Crosstalk - Willis, Connie (Del Rey, 2016)
"One of science fiction's premiere humorists turns her eagle eye to the crushing societal implications of telepathy. In a not-too-distant future, a simple outpatient procedure that has been promised to increase empathy between romantic partners has become all the rage. So when Briddey Flannigan's fiancé proposes that he and Briddey undergo the procedure, she is delighted! Only...the results aren't quite as expected. Instead of gaining an increased empathetic link with her fiancé Briddey finds herself hearing the actual thoughts of one of the nerdiest techs in her office. And that's the least of her problems"--